INDIVIDUALIZED YEARLY WAGE INCREMENT RATE BASED ON PERSONAL CONSUMPTION WITH ITEMIZED CPI - Kok-Leong, Soo; Chai-Thing, Tan; You-How, Go; Hui-Wen, Cheah; Teh Hong Piow, (Malaysian Journal of Business and Economics (MJBE), 2025)
The public often perceives a higher inflation rate than the one announced by authorities. As a result, individuals tend to seek larger increases in their annual wages compared to the reported inflation rate. However, comparing these two rates is often meaningless, as people primarily focus on the absolute prices of goods in their daily purchases. A more practical measure of inflation would account for individual consumption patterns through the consumer price index. This approach could serve as a more reliable reference for assessing living costs and guiding annual wage increases to maintain financial stability. The main findings indicate that the generally perceived inflation rate is typically 2 to 3 times higher than the officially announced rate. Most wage increases fall below RM1,000, with some ranging from RM1,500 to RM2,000. The average wage increase is RM473, with a standard deviation of RM402. Notably, the actual yearly wage increases (in RM) exceed the individualized wage increments. This suggests that the wage increases currently being provided to most employees are sufficient to cover their expenses, based on the inflation rate reported by authorities.